2012
DOI: 10.14301/llcs.v3i3.198
|View full text |Cite
|
Sign up to set email alerts
|

Can we spot deleterious ageing in two waves of data? The Lothian Birth Cohort 1936 from ages 70 to 73

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Internal consistency/short-term test-retest stability for Inspection Time was unavailable. We therefore indicate that the reliability of Inspection Time is greater than or equal to its 3-year test-retest stability, which is reported inJohnson et al (2012).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Internal consistency/short-term test-retest stability for Inspection Time was unavailable. We therefore indicate that the reliability of Inspection Time is greater than or equal to its 3-year test-retest stability, which is reported inJohnson et al (2012).…”
mentioning
confidence: 64%
“…In such instances, more prolonged longitudinal intervals would be necessary for systematic changes to accumulate to the degree that correlations become detectable. Indeed, based on previous simple difference score analyses of single cognitive tests and other single variables in these LBC1936 data, Johnson et al (2012) concluded that "two waves of longitudinal data were not sufficient to assess meaningful patterns of ageing" (p. 312).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial long-term relations in the opposite direction have also been found, for example, with childhood intelligence predicting late-life emotional stability (Gow, Whiteman, Pattie, & Deary, 2005). Therefore, future studies should consider operationalizing even wider time spans than the 12 years investigated in this study and including more than two measurement occasions, because two assessments may not be sufficient to capture and describe meaningful patterns of aging as well as the unfolding of processes and their interrelation over time (Johnson et al, 2012; Kenny, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, the availability of more measurement occasions would have been desirable. According to Kenny (2005), the unfolding of processes and their interrelations over time may not be sufficiently informed (and described) based on two assessments only (see also Johnson et al, 2012). Therefore, future studies including more measurement occasions are necessary.…”
Section: Discussionmentioning
confidence: 99%